PRODUKSI BETA-1,3 GLUKAN DARI Agrobacterium DAN AKTIVITAS PENYEMBUHAN LUKA TERBUKA PADA TIKUS PUTIH - Kusmiati, Kusmiati; Rachmawati, Fitria; Siregar, Syafrida; Nuswantara, Sukma; Malik, Amarila (Makara Journal of Science, 2006)
Production of beta-1,3 glucan from Agrobacterium and its wound healing activity on white rat. The objective of this study was to determine the activity of beta-1,3 glucan product extracted from local Agrobacterium sp Bro 1.2.1, both wild-type and mutant-type, on opened-wound healing process. Beta-1,3 glucan product was extracted by precipitation, and the purification was carried out by column chromatography as KCl gradient fractions. In this study, white Sprague Dawley rats were employed, and have been treated for opened-wound condition. Seven groups were performed in this experiment, i.e. the negative control, the positive control employing povidone iodine, the two groups of two commercial beta-1,3 glucan with 0,02 mg/4 cm2 each, and the last three groups of beta-1,3 glucan as the test group with 0,02 mg/4 cm2, 0,10 mg/4 cm2 and 0,50 mg/4 cm2, respectively. The result showed significant differences of wound-healing activity performing statistical analysis of the least significance between the negative control, the positive control, as well as the highest dose of the test group of beta-1,3 glucan, at the dose of 0,5 mg/4 cm2 (p<0.05).